Overview and ecological inundation plan of the Tóvár Landscape Protection District - Kállai, Szabolcs (JOURNAL OF LANDSCAPE ECOLOGY, 2004)
The target area has special conservation value and increased threat of inland inundations in our small landscape unit of Bereg. The significant inland inundations of last years called public’s attention. After these inundations there were possibilities to apply for funds in ministries to solve the same and similar inland inundation problems. The problem of inland inundation might be solved by the result of these tenders but the protection of conservation values remained in the background. The present work would like to call attention on the importance of the cooperation between nature protection and water management. In order to solve the ecological problems of the Ukrainian Tóvár Landscape Protection District I suggest an ecological inundation plan. It would cease the cause of disappearance of birds and plants and to make a chance for the reintroduction of these species. The ecological inundation plan was based on the network of the Bereg inland water system and on the methods of integrated water management.
Keywords: inland water system; ecological problem; integrated water management; ecological purpose inundation plan